1985
DOI: 10.1111/j.1440-1819.1985.tb01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr Virus Antibodies in Neurological Diseases

Abstract: Antibody titers to the Epstein-Barr virus (EBV) in the serum and cerebrospinal fluid (CSF) were determined in 57 cases of acute or subacute neurological diseases. As a result, sera from 11 cases (7 Bell's palsy, 2 encephalitis and 2 acute cerebellar ataxia) were found to be positive for antibodies to early antigen. Seven of these 11 cases either seroconverted for IgG antibodies to viral capsid antigen (VCA) or were proven positive for anti-VCA-IgM antibodies in the serum. While 4 were found positive for IgG an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Acute EBV infections account for approximately 2 to 5% of infection-related neurological diseases [Yabuki et al, 1985;Bale, 1999], and a similar rate (2/48) was observed in the present study. Reactivated or chronic active EBV infections, in contrast, were found in 17% (8/48) of our patients.…”
Section: Discussionsupporting
confidence: 87%
“…Acute EBV infections account for approximately 2 to 5% of infection-related neurological diseases [Yabuki et al, 1985;Bale, 1999], and a similar rate (2/48) was observed in the present study. Reactivated or chronic active EBV infections, in contrast, were found in 17% (8/48) of our patients.…”
Section: Discussionsupporting
confidence: 87%
“…Positive EBV serological test result has previously been reported in patients with Bell's palsy 8. Excluding acute EBV infection might be helpful in the diagnosis of patients with facial palsy, particularly when bilateral, even in cases with no systemic manifestations of EBV infection.…”
Section: Discussionmentioning
confidence: 90%
“…Acute EBV infections account for approximately 2% to 5% of infection-related neurological diseases [2,3]. Hausler et al [4] investigated 48 pediatric patients with neurological complications of acute and persistent EBV infection and reported a similar (4%; 2/48) rate of infection-related neurological disease.…”
mentioning
confidence: 96%
“…
Infectious mononucleosis is a benign, self-limiting disorder caused by primary Epstein-Barr virus (EBV) infection. Various neurological diseases, such as encephalitis, meningitis, acute inflammatory polyneuropathy, Bell's palsy, and peripheral neuropathy, may be associated with EBV infection; however, involvement of the central nervous system (CNS) is relatively uncommon [1][2][3][4][5]. Rare cases of hypoglossal nerve palsy associated with acute EBV infection have been reported in children [6][7][8][9].
…”
mentioning
confidence: 99%